Siltation negatively affects settlement and gaping behaviour in eastern oysters. (August 2021) - Poirier, Luke A.; Clements, Jeff C.; Coffin, Michael R.S.; Craig, Tessa; Davidson, Jeff; Miron, Gilles; Davidson, John D.P.; Hill, Jonathan; Comeau, Luc A.
Abstract: While high levels of siltation are known to be deleterious to eastern oysters ( Crassostrea virginica ), the collective effect of suspended and bedded sediment is understudied from the perspective of oyster farming and bed restoration. In this study, we used laboratory experiments to explore spat settlement rates on a wild bed proxy substrate (i.e., empty shells on the bottom of experimental tanks) in conditions simulating a siltation event and the presence of suspended spat collectors. Using high-frequency valvometry, we also described the behavioural effects of acute sediment burial on wild adult oysters in situ . The vast majority of larvae settled on bottom substrate as opposed to suspended collectors. Sediment negatively affected overall oyster spat settlement on bottom shell, as spat densities were ≈3 × lower when sediment was present. This negative effect was largely attributed to severely depressed spat densities on the upper side (top) of bottom shells. Settlement on the underside of bottom shell was less affected. Wild adult oyster behaviour was negatively affected by acute burial, which ultimately resulted in death. We suggest that the reduction in settlement in the presence of siltation is likely due to the combined effects of suspended sediment on cue detection and bedded sediment on substrate availability. Given that oysters are ecosystem engineers, the negative effects of siltation on both larval and adult oysters can ultimately result in cascading effects to the surrounding biological community. Highlights: Tested effect of silt on oyster larval settlement to artificial collectors and natural shell substrate. Compared settlement on upper and under side of benthic shell substrate. Examined adult oyster health during an acute siltation event. Settlement higher on benthic shell than suspended substrate; silt negatively affected settlement and adult health. Negative effects of siltation were less severe on underside of benthic shell.